2015
DOI: 10.1016/j.tra.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between logistics infrastructure and trade: Evidence from Spanish regional exports

Abstract: Geographical factors and transport infrastructure are two of the key determinants that influence international competitiveness. In this sense, the quality of such infrastructure and how widespread it is, the distribution and capacity of logistics facilities in a country, as well as the number of private operators and their degree of specialisation, all play an increasingly important role in the design of business strategies aimed at increasing a country's share of the international market. Until recently, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 33 publications
(38 reference statements)
6
101
1
6
Order By: Relevance
“…The current literature about the regional effect of infrastructure on trade has mainly focused on logistics (Alama, Marquez, Navarro, & Suarez, ; Alama, Marquez, & Suarez, ; Márquez‐Ramos, ) rather than ICT infrastructure. The only exception is Bensassi, Marquez, Martinez, and Suarez (), who incorporate ICT infrastructure, but they only study regional exports from Spain and the priority of the study is logistics, in line with the previous literature. Given that European integration is a wide process that affects European regions as a whole, the inclusion of the highest possible number of regions provides an accurate and consistent explanation of trade patterns and how ICT infrastructure affects them.…”
Section: Introductionmentioning
confidence: 76%
“…The current literature about the regional effect of infrastructure on trade has mainly focused on logistics (Alama, Marquez, Navarro, & Suarez, ; Alama, Marquez, & Suarez, ; Márquez‐Ramos, ) rather than ICT infrastructure. The only exception is Bensassi, Marquez, Martinez, and Suarez (), who incorporate ICT infrastructure, but they only study regional exports from Spain and the priority of the study is logistics, in line with the previous literature. Given that European integration is a wide process that affects European regions as a whole, the inclusion of the highest possible number of regions provides an accurate and consistent explanation of trade patterns and how ICT infrastructure affects them.…”
Section: Introductionmentioning
confidence: 76%
“…In order to estimate the impact of logistics on international trade, the augmented gravity model, including logistics variables, was generally used in the former studies [3]. Generally, there are three determinative variables affecting trade flows between any two economies:…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…They found that port efficiency improvement can reduce transportation costs and increase bilateral trade volume. Bensassi et al [3] studied the relationship between logistics infrastructure and trade in Spain and found that the number, size, and quality of logistics infrastructure positively affect export volume.…”
Section: Logistics Performance and International Tradementioning
confidence: 99%
“…As can be seen from Fig.5, six distribution centers (25,18,13,5,12,9) are selected in the 30 customers location with the weight by demand, the 25-th distribution center can supply the demand for six customers (1,2,16,19,23,26), the 18-th distribution center can supply the demand for two customers (28,29), the 13-th distribution center can supply the demand for six customers (6,15,14,18,27,30), the 5-th distribution center can supply the demand for six customers (7,21), the 12-th distribution center can supply the demand for six customers (3,4,8,11,17,24), and the 9-th distribution center can supply the demand for two customers (10,22).…”
Section: Simulation Experiments and Analysismentioning
confidence: 99%
“…With the rapid development of world economy and the development of science and technology, now logistics distribution as an emerging service is developing rapidly in the world [1][2]. An advanced logistics distribution system can not only accelerate the rate of economic growth, but also reduce unnecessary transaction cost.…”
Section: Introducementioning
confidence: 99%